Re-Listening to Derrida and Benjamin - Caroline Wilkins (Performance Philosophy, 2023)
News on the publication of Two Plays for the Stage was announced on the Performance Philosophy website during 2021 but only received my attention this year, when I ordered a copy of the book out of curiosity. After reading it and making copious notes, I contacted the two authors to give them my impressions, particularly those concerning my responses to it in terms of sound. The trigger for this ReView came from an email discussion with John Schad on critical-creative writing, which I interpret as creative criticism, meaning that this could take any form appropriate to the artist’s discipline. Indeed my essay in an earlier edition of the journal (Wilkins, 2016) took the form of a labyrinthine script during its writing process, this as a response to Freddie Rokem's initial article (Rokem, 2015). It later manifested itself in an audio piece presented in Vol. 7.1, a collaboration between myself and Leona Jones entitled With W/Ringing Ears. (Jones, Wilkins, 2022). Fred Dalmasso’s research into the syncope (2017), which surfaces within the concluding essay to the book, has interested me for some time in terms of its possible parallels in the world of sound.